Unusual variation in musculocutaneous nerves - Bhattarai, C; Poudel, PP (Kathmandu University Medical Journal, 2010)
Background: Variations in origin, course, branching pattern, termination and connections of the musculocutaneous nerve in the arm are not as uncommon as was once thought. Variational study of nerve in Nepalese is very less and can be of surigical-clinical importance. This opinion led us to performing this study. Objectives: The aim of this study was to a study in Nepalese which could be important for clinical investigation and the surgical treatment of peripheral nerve injury. Materials and methods: This study was carried out in Manipal College of medical sciences (MCOMS). Dissection of formalised 16 cadavers (n=32 upper limbs) were carried out using normal dissection kit with the help of standard dissection manual in two and half years. Results: The study revealed the variation in course, branching pattern and termination of musculocutaneous nerve in 6.25% of cases unilaterally on the right side. No statistically significant differences by gender and side were observed. Conclusion: This present study provides the evidence of variation of musculocutaneous nerve in Nepalese. The knowledge of the anatomical variations of the peripheral nerve system can help explain an incomprehensible clinical sign. Key words: Musculocutaneous nerve; Median nerve; Brachial plexus; Peripheral nerve repair. DOI: 10.3126/kumj.v7i4.2763 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 408-410